Compelling Compromise: Canada chooses Conciliation over Arbitration 1900-1907 - Webber, Jeremy (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1991)
Abstract This paper examines the origins of Canada's labour policy during the first years of this century. It explains why the Canadian government rejected arbitration as the chief means of settling labour disputes, adopting conciliation instead. This choice lies at the foundation of Canadian labour law: governments since that time have sought to dampen industrial conflict by pushing the parties to compromise they have generally balked at imposing specific terms of employment The argument proceeds in three stages. It first reviews the formation of Canadian labour policy during the years 1900 to 1907. It then identifies the specific reasons for the government's rejection of arbitration. Finally, it suggests structural characteristics of the Canadian political economy which favoured the choice of conciliation over arbitration.